Electronic Cigarette Exposure Enhances Lung Inflammatory and Fibrotic Responses in COPD Mice - Han, Hongwei; Peng, Guangda; Meister, Maureen; Yao, Hongwei; Yang, Jenny J.; Zou, Ming-Hui; Liu, Zhi-Ren; Ji, Xiangming (Frontiers in Pharmacology, 2021)
Although a few studies show that the use of electronic nicotine delivery systems (ENDS) may ameliorate objective and subjective outcomes in COPD smokers who switched to electronic cigarettes, it is unclear whether e-cigarette exposure alters lung pathological features and inflammatory response in COPD. Here, we employed βENaC-overexpressing mice bearing COPD-like pulmonary abnormality, and exposed them to ENDS. We found that ENDS exposure aggravated airspace enlargement and mucus production in βENaC-overexpressing mice, which was associated with increased MMP12 and Muc5ac, respectively. ENDS exposure to mice significantly increased the numbers of macrophages, particularly in M2 macrophages in bronchoalveolar lavage (BAL) fluid, despite ENDS did not induce M2 macrophage polarization in a cultured murine macrophage cell line (RAW264.7). There were no changes in neutrophils in BAL fluid by ENDS exposure. Multiple cytokine productions were increased including M-CSF, IL-1rα, IL-10, and TGF-β1, in BAL fluid from mice when exposed to ENDS. The Sirius Red staining and hydroxyproline assay showed ENDS-exposed mice displayed enhanced fibrotic phenotypes compared to control mice. In conclusion, ENDS exposure enhances airspace enlargement, mucus secretion, and fibrogenesis in COPD mice. This is associated with increased MMP12, inflammatory responses, and M2 macrophage phenotype. This study provides pre-clinical data implicating that electronic cigarette exposure is not safe in COPD patients who want to replace traditional cigarettes with ENDS.